Economics in Spirit and Truth - Wariboko, N. author. aut Link
XX, 225 p.
Keywords: Wariboko offers a critical-philosophical perspective on the logics and dynamics of finance capital in the twenty-first century in order to craft a model of the care of the soul that will enable citizens to not only better negotiate their economic existences and moral evaluations within it, but also resist its negative impact on social life.